Discover a world of knowledge at Westonci.ca, where experts and enthusiasts come together to answer your questions. Ask your questions and receive detailed answers from professionals with extensive experience in various fields. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.

What translation rule can be used to describe the result of the composition of (x, y) → (x-9, y
-2) and (x, y) + (x + 1, y-2)?
(x, y) = (x+8, y– 4)
(x, y) = (x – 10, y +0)
(x, y) → (x–8. y - 4)
(x, y) = (x - 4. y - 8)


Sagot :

Answer: Choice C

[tex](x,y) \to (x-8,y-4)[/tex]

===================================================

Explanation:

The first translation [tex](x,y) \to (x-9,y-2)[/tex] has x become x-9. This means we shift 9 units to the left.

The second translation [tex](x,y) \to (x+1,y-2)[/tex] tells us to shift 1 unit to the right when going from x to x+1.

Combining the "9 units to the left" and "1 unit to the right" will produce an overall shift of "8 units to the left". It might help to draw out a number line to see this.

After combining those two translations, we'll have [tex]x \to x-8[/tex] which means we'll end up with [tex](x,y) \to (x-8,y-4)[/tex]. The first two translations shift the point down 2 units at a time, so overall we shift down 4 units.